How negative labor supply shocks affect training in firms : lessons from opening the Swiss-German border - Neuber-Pohl, Caroline [Verfasser]; Pregaldini, Damiano [Verfasser]; Backes-Gellner, Uschi [Verfasser]; Dummert, Sandra [Verfasser]; Pfeifer, Harald [Verfasser] (My University, 2023)
„By exploiting a sharp outflow of German workers to Switzerland after the opening of borders, we examine the impact of an exogenous negative labor supply shock on training in firms. In Germany this training takes place in the form of apprenticeships. Using detailed administrative data for both sides of the border, we find that the negative supply shock of skilled workers leads to an increase in the number of apprentices in firms in Germany despite a significant decrease in apprentice wages. These two effects can be explained with a standard two-factor production model. Our results suggest that firms react by substituting out-flowing skilled workers with newly trained apprentices. Moreover, the apprentice supply increased because adolescents react to the better employment prospects due to the open borders. The results complement recent studies on the effects of negative labor supply shocks and provide important empirical evidence for the functioning of training markets.“ (authors‘ abstract; BIBB-Doku)
Keywords: G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; S 3.2 Unternehmen und Behörden; G 1.3.1.1 Ausbildungsstellenmarkt; 370; 330; Arbeitsmarkt; Arbeitskräfteangebot; Arbeitsmigration; Einflussfaktor; Berufsausbildung; Ausbildungsverhalten; Ausbildungsbereitschaft; Ausbildungsplatzangebot; Grenzgebiet; Bundesrepublik Deutschland; Schweiz